Improving children's oral health through assessment, prevention, and treatment - Ngwu, Chika Charity; Adamu, VE; Eneh, C. K. (Orapuh Journal, 2021)
The health of the mouth of children says a lot about their general health. Since it is a fact that what affects the mouth can also affect the general health of the body, it follows that any improvements in the health of the mouth will, inadvertently, bring about some gains in general health. Consequently, it is of utmost importance that we bring to bear upon the health of children, all the recent giant strides that have been made in the areas of genomics, biological, behavioral, social, and health services research, which have strengthened the evidence base available to support initiatives and translational efforts. To translate the available researches into policies and practices that may have positive impacts upon the health of children, there exists the need to support current guidelines with extra efforts to ensure that children receive better care. The purpose of this paper was to assess the need to improve children's oral health through assessment, prevention, and treatment. Issues such as oral health assessment and oral disease prevention strategies that can be adopted to combat children’s oral health challenges are also highlighted. Treatment modalities are equally addressed.